Amelioration of steatohepatitis with pentoxifylline in a novel nonalcoholic steatohepatitis model induced by high-fat diet - Yalniz, Mehmet; Bahcecioglu, I. Halil; Kuzu, Nalan; Celebi, Selman; Ataseven, Huseyin; Ustundag, Bilal; Şahin, Kazım (Springer, 2007)
We sought to evaluate the effects of pentoxifylline (PTX) on steatohepatitis in a novel experimental nonalcoholic steatohepatitis (NASH) model induced by a high-fat diet (HFD). Thirty-three male Sprague-Dawley rats were randomly divided into 3 groups. The first group received only standard rat diet (control group); groups 2 (placebo group) and 3 were given HFD, ad libitum. After week 4, 0.5 mL of physiologic serum was injected subcutaneously to the placebo group and 50 mg/kg/d PTX was given intraperitoneally to the third group (group PTX). After 6 weeks all rats were humanely killed. Serum biochemistry, tumor necrosis factor-alpha (TNF-alpha), plasma, and liver tissue malondialdehyde (MDA) were analyzed. Histopathologically, steatosis, ballooning degeneration, inflammation, and fibrosis were determined. Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels, plasma and liver tissue MDA, and plasma TNF-alpha levels were significantly higher in placebo group than in the control group. Tumor growth factor-beta levels, however, were comparable in the placebo and control groups. On histopathologic examination, steatosis, inflammatory cells per square millimeter, and ballooning degeneration were significantly higher in the placebo group than in the control group. No fibrosis or Mallory bodies were found in the placebo group. AST, ALT, plasma and liver tissue MDA, and plasma TNF-alpha levels were significantly lower in PTX group compared to the placebo group. Histopathologically, steatosis, mean number of inflammatory cells/mm(2) and ballooning degeneration in PTX group were also significantly lower than in the placebo group. In conclusion, PTX strikingly ameliorates steatohepatitis in this novel NASH model not only by inhibiting the TNF-alpha but also suppressing the oxidative stress markers.
Keywords: nonalcoholic steatohepatitis; novel experimental model; pentoxifylline